Hybrid molecules inhibiting myeloperoxidase activity and serotonin reuptake: a possible new approach of major depressive disorders with inflammatory syndrome. (27th March 2014) - Soubhye, Jalal; Aldib, Iyas; Prévost, Martine; Elfving, Betina; Gelbcke, Michel; Podrecca, Manuel; Conotte, Raphaël; Colet, Jean‐Marie; Furtmüller, Paul G.; Delporte, Cédric; Rousseau, Alexandre; Vanhaeverbeek, Michel; et al.
Abstract Objectives Major depressive disorder (MDD) is accompanied with an imbalance in the immune system and cardiovascular impairments, such as atherosclerosis. Several mechanisms have been pointed out to underlie this rather unexpected association, and among them the activity of myeloperoxidase (MPO). The aim of our study was to find compounds that inhibit both MPO and serotonin transporter (SERT) for treating MDD associated with cardiovascular diseases. Methods SERT inhibition was assessed with measuring of [3H]‐serotonin uptake using HEK‐293 MSR cells. MPO inhibition was determined by taurine chloramine test on 3‐(aminoalkyl)‐5‐fluoroindole derivatives and on clinically relevant antidepressants. All kinetic measurements were performed using a temperature‐controlled stopped‐flow apparatus (model SX‐18 MV). Promising lead compounds were docked onto SERT 3D structure modelled using the LeuT structure complexed to tryptophan (PDB code 3F3A). Their toxicological profile was also assessed. Key findings 3‐(aminoalkyl)‐5‐fluoroindole derivative with 5 carbons on the side chain and paroxetine showed the best activity on both MPO and SERT at the nanomolar range. Paroxetine was found to be the first irreversible MPO inhibitor at nanomolar concentrations. Conclusions Our results put forward the first hybrid molecule (compound 25) and drug (paroxetine) that can be especially used in MDD associated with inflammatory syndrome.